Nucleosomes are well positioned in exons and carry characteristic histone modifications - Andersson, Robin; Enroth, Stefan; Rada-Iglesias, Alvaro; Wadelius, Claes; Komorowski, Jan (Genome Research, 2009)
The genomes of higher organisms are packaged in nucleosomes with functional histone modifications. Until now, genome-wide nucleosome and histone modification studies have focused on transcription start sites (TSSs) where nucleosomes in RNA polymerase II (RNAPII) occupied genes are well positioned and have histone modifications that are characteristic of expression status. Using public data, we here show that there is a higher nucleosome-positioning signal in internal human exons and that this positioning is independent of expression. We observed a similarly strong nucleosome-positioning signal in internal exons of Caenorhabditis elegans. Among the 38 histone modifications analyzed in man, H3K36me3, H3K79me1, H2BK5me1, H3K27me1, H3K27me2, and H3K27me3 had evidently higher signals in internal exons than in the following introns and were clearly related to exon expression. These observations are suggestive of roles in splicing. Thus, exons are not only characterized by their coding capacity, but also by their nucleosome organization, which seems evolutionarily conserved since it is present in both primates and nematodes.